2022
DOI: 10.3390/rs14215584
|View full text |Cite
|
Sign up to set email alerts
|

Soil Moisture Prediction from Remote Sensing Images Coupled with Climate, Soil Texture and Topography via Deep Learning

Abstract: Soil moisture (SM) is an important biophysical parameter by which to evaluate water resource potential, especially for agricultural activities under the pressure of global warming. The recent advancements in different types of satellite imagery coupled with deep learning-based frameworks have opened the door for large-scale SM estimation. In this research, high spatial resolution Sentinel-1 (S1) backscatter data and high temporal resolution soil moisture active passive (SMAP) SM data were combined to create sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(7 citation statements)
references
References 69 publications
0
2
0
Order By: Relevance
“…Wang et al ( 2022 ) showed that the accuracy of the yield estimation results of LSTM was generally better than those of conventional ML methods. Celik et al ( 2022 ) investigated soil moisture forecasting based on satellite-derived data with LSTM and they obtained accurate soil moisture values for the next day. Previous research on weather-induced vegetation stress forecasting using LSTM involves utilizing precipitation-based drought indices, such as Standardized Precipitation Index (SPI), Standardized Precipitation Evapotranspiration Index (SPEI), or combining them with other hydro-meteorological factors such as temperature, humidity, and wind speed (Vo et al 2023 ; Wu et al 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Wang et al ( 2022 ) showed that the accuracy of the yield estimation results of LSTM was generally better than those of conventional ML methods. Celik et al ( 2022 ) investigated soil moisture forecasting based on satellite-derived data with LSTM and they obtained accurate soil moisture values for the next day. Previous research on weather-induced vegetation stress forecasting using LSTM involves utilizing precipitation-based drought indices, such as Standardized Precipitation Index (SPI), Standardized Precipitation Evapotranspiration Index (SPEI), or combining them with other hydro-meteorological factors such as temperature, humidity, and wind speed (Vo et al 2023 ; Wu et al 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Under controlled irrigation, Liu et al (2018) found that SIF and indices calculated at wavelengths between 680 nm and 750 nm are related to soil moisture at different depths and exhibit different response times on wheat. Therefore, it should be noted that the responses of spectral indices to soil water profile and response times depend on the climatic regimes of the study area, the type of vegetation and its phenological stage, the depth and distribution of the roots, the soil physical characteristics and the spatial scale of the observation (Celik et al 2022;Li et al 2022;Liu et al 2018;Pablos et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Soil moisture (SM) monitoring plays a crucial role in the context of many branches, with the main impact on agriculture around the world [1][2][3], as a deficit of water available for plants is the main factor governing the agricultural drought assessment [4]. On the other hand, soil moisture monitoring is a still widely explored issue in the research world [5][6][7][8]. For the tens of years of space exploration, soil monitoring techniques have been expanded to include an additional research area focusing on the harmonisation and fusion of soil moisture data obtained at different spatial and temporal scales [9][10][11].…”
Section: Introductionmentioning
confidence: 99%